Heuristic optimisation for network restoration and expansion in compliance with the single‐contingency policy. Issue 17 (20th September 2017) - Thurner, Leon; Scheidler, Alexander; Probst, Alexander; Braun, Martin
Abstract : Since failure of high‐ to medium‐voltage (MV) transformers affect a large number of consumers, they are usually built with a redundancy to guarantee service restoration in the case of a single contingency. The redundancy can be provided by a backup transformer or by transferring the load to a neighbouring substation in case of failure. While a load transfer allows for more efficient use of transformers in normal operation, it also requires the MV network to be dimensioned with redundant transmission capability for the contingency case. In this study, the authors present their approach to determine if it is profitable in the long term to remove a backup transformer in intrinsically safe substations and handle resupply with load transfer to neighbouring substations instead. To this end, they compare the cost of the necessary network expansion to the costs of a backup transformer. They introduce an iterated local search algorithm for the calculation of emergency switching plans as well as expansion of the MV network. The methodology is applied to a large real MV network group, where reinforcing the network to allow a load transfer is cost efficient compared with the existing backup transformer in three of four substations.